Cardioprotective properties of opioid receptor agonists in rats with stress-induced cardiac injury - Prokudina, E. S; Maslov, L. N; Naryzhnaya, N. V; Tsibulnikov, S. Y; Lishmanov, Y. B; Madias, J. E; Oeltgen, P. R (Physiological research, 2019)
The objectives of this study were to investigate the role of endogenous opioids in the mediation of stress-induced cardiomyopathy (SIC), and to evaluate which opioid receptors regulate heart resistance to immobilization stress. Wistar rats were subjected to 24 h immobilization stress. Stress-induced heart injury was assessed by 99mTc-pyrophosphate accumulation in the heart. The opioid receptor (OR) antagonists (naltrexone, NxMB - naltrexone methyl bromide, MR 2266, ICI 174.864) and agonists (DALDA, DAMGO, DSLET, U-50,488) were administered intraperitoneally prior to immobilization and 12 h after the start of stress. In addition, the selective micro OR agonists PL017 and DAMGO were administered intracerebroventricularly prior to stress. Finally pretreatment with guanethidine was used. Naltrexone did not alter the cardiac 99mTc-PP accumulation in stressed rats. NxMB aggravated stress-induced cardiomyopathy (P=0.005) (SIC). The selective micro OR agonist DALDA, which does not cross the blood-brain barrier, completely prevented (P=0.006) SIC. The micro OR agonist DAMGO exhibited weaker effect than DALDA. The selective delta ligand (DSLET) and kappa OR ligand (U-50,488) did not alter stress-induced 99mTc-pyrophosphate accumulation in the heart. Intracerebroventricular administration of the micro OR agonists aggravated SIC. Pretreatment with guanethidine abolished this effect (P=0.01). Guanethidine alone exhibited cardioprotective properties. A stimulation of central micro OR promotes an appearance of SIC. In contrast, stimulation of peripheral micro OR contributes to an increase in cardiac tolerance to stress.
Keywords: Naltrexone; Animals; naltrexon; narkotika - antagonisté; kardiotonika; Analgesics, Opioid; Rats, Wistar; psychický stres; Narcotic Antagonists; Heart Diseases; Enkephalin, Ala(2)-MePhe(4)-Gly(5)-; opioidní analgetika; Receptors, Opioid, mu; Immobilization; Male; Stress, Psychological; krysa rodu Rattus; imobilizace; receptory opiátové mu; Cardiotonic Agents; zvířata; mužské pohlaví; Myocardium; myokard; enkefalin, Ala(2)-MePhe(4)-Gly(5)-; Rats; potkani Wistar; nemoci srdce